(untitled) (Comprehensive Journal of Science, 2025)
This study aims to analyze the contribution of electronic accounting information systems in enhancing financial performance within institutions. It focuses on the effectiveness of these systems in rationalizing expenditures, improving the efficiency of financial operations, and supporting high-quality decision-making. The descriptive-analytical approach was adopted, relying on secondary sources such as books and relevant academic studies to build the theoretical framework of the study, in addition to analyzing the actual use of electronic accounting systems in a real institutional context. The study concluded that electronic accounting information systems play a central role in improving financial performance by providing accurate data, speeding up the preparation of financial reports, and offering a high ability to detect accounting errors. These factors contribute significantly to enhancing the quality of financial and administrative decisions. The results also showed a strong and statistically significant correlation between the implementation of such systems and the improvement of institutional financial performance. In light of these findings, the study recommends adopting advanced electronic accounting systems and continuously updating them, due to their direct impact on enhancing financial efficiency and improving the accuracy of financial forecasting and analysis